Hubungan konformitas teman sebaya dengan motivasi belajar siswa SMP Muhammadiyah - Mukhlis Habibullah; Enik Nurkholidah (SCHOULID: Indonesian Journal of School Counseling, 2022)
This study aims to see and determine the relationship between peer conformity and learning motivation.The study was conducted at SMP Muhammadiyah 1 Mlati Sleman in the academic year 2021/2022. This research was a primary research with a proportional random sampling design and a sample of 129 class VIII students was obtained. The measurement uses primary data, which is distributing questionnaires to the sampel. The analytical technique used to prove the hypothesis is to test the classical assumptions and test the pearson product moment correlation. The results showed that peer conformity has a very strong influence on student learning motivation. This is evidenced by the Pearson Correlation value of -0.011 and a significance value of 0.899.